Effect of atorvastatin on orthodontic tooth movement in male wistar rats. - Amir Hossein MirHashemi; Maryam Afshari; Mojgan Alaeddini; Shahroo Etemad-Moghadam; Ahmadreza Dehpour; Sedigheh Sheikhzade; Mohammad Sadegh Ahmad Akhoundi (Tehran University of Medical Sciences, 2013)
Statins are used as cholesterol-lowering drugs by many patients and have been recently shown to affect bone metabolism. The aim of this study was to determine the effect of atorvastatinon on orthodontic tooth movement (OTM) in rats.Thirty-six adult male Sprague-Dawley rats were randomly divided into three groups of 12 samples each. Group A, served as control with no medication while groups B and C received a daily gavage of carboxymethyl cellulose (CMC) as vehicle and atorvastatin (5 mg/kg) as test substance, respectively. In all three groups, 6mm nickel-titanium closed-coil springs were ligated between the maxillary incisors and first left molars to deliver an initial force of 60g. Tooth movement was measured following sacrifice, 21 days after appliance insertion. Root resorption, PDL width and osteoclast number were histologically evaluated and compared between the groups.The mean amount of tooth movement was 0.62 mm in group A, 0.59 mm in group B and 0.38 mm in group C. OTM reduction following administration of atorvastatin was statistically significant (p0.05).According to the results obtained in the current study, atorvastatin appears to reduce tooth movement in rats; however its effect on osteoclasts, especially osteoclastic function, requires further investigation.